The Association between Obesity and Outcomes in Critically Ill Patients - Stephan Wardell; Alastair Wall; Rhonda Bryce; John A Gjevre; Karen Laframboise; John K Reid (Canadian Respiratory Journal)
BACKGROUND: Obesity rates are increasing worldwide, particularly in North America. The impact of obesity on the outcome of critically ill patients is unclear.